2015
DOI: 10.1016/j.ebiom.2015.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Low Red Blood Cell Vitamin C Concentrations Induce Red Blood Cell Fragility: A Link to Diabetes Via Glucose, Glucose Transporters, and Dehydroascorbic Acid

Abstract: Strategies to prevent diabetic microvascular angiopathy focus on the vascular endothelium. Because red blood cells (RBCs) are less deformable in diabetes, we explored an original concept linking decreased RBC deformability to RBC ascorbate and hyperglycemia. We characterized ascorbate concentrations from human and mouse RBCs and plasma, and showed an inverse relationship between RBC ascorbate concentrations and deformability, measured by osmotic fragility. RBCs from ascorbate deficient mice were osmotically se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 77 publications
(142 reference statements)
0
98
1
Order By: Relevance
“…It has been demonstrated that pharmalogical doses of Vitamin C would relieve hemolysis within patients that suffered from G6PD deficiency [12][13][14]. Nonetheless, it was undeniable that over-dose Vitamin C could also contribute to aggravated haemolysis of G6PD-deficient erythrocytes, as reported in both case reports and mechanism researches [15][16][17]. Thus, this study was intended to investigate the eryptosis conditions among the population with G6PD deficiency or nomal activity habituated in Daidehong prefecture of Yunnan province and to explore the inherent mechanisms with in-vitro erythrocytes that were treated with proper concentrations of Vitamin C and hydrogen peroxide.…”
Section: Introductionmentioning
confidence: 75%
“…It has been demonstrated that pharmalogical doses of Vitamin C would relieve hemolysis within patients that suffered from G6PD deficiency [12][13][14]. Nonetheless, it was undeniable that over-dose Vitamin C could also contribute to aggravated haemolysis of G6PD-deficient erythrocytes, as reported in both case reports and mechanism researches [15][16][17]. Thus, this study was intended to investigate the eryptosis conditions among the population with G6PD deficiency or nomal activity habituated in Daidehong prefecture of Yunnan province and to explore the inherent mechanisms with in-vitro erythrocytes that were treated with proper concentrations of Vitamin C and hydrogen peroxide.…”
Section: Introductionmentioning
confidence: 75%
“…Thus, it may be speculated that the degree of glycemic control and, consequently, the level of oxidative stress and ascorbate oxidation rate may affect the bioavailability of vitC in T1DM pregnant women through competitive inhibition of DHA transport as proposed by Mann and Newton already in 1975 [52] and supported by the NHANES study 2003–2006 data [53]; here an inverse relationship between vitC and HbA1c was reported in 7697 non-diabetic participants. Moreover, Tu et al have recently proposed that impaired red cell recycling of DHA may be a key link in diabetes [54]. …”
Section: Discussionmentioning
confidence: 99%
“…Saturation of lymphocytes with AA has also been reported to improve immune competence. 49 An inverse relationship exists between RBC ascorbic acid concentration and osmotic fragility. 47 Dietary increase in AA has also been shown to result in saturating levels of AA and in a notable increase in complement C1q compared to normal or suboptimal intake.…”
Section: Haematological Analysismentioning
confidence: 99%